Rifampicin induced shock during re-exposure for treatment of latent tuberculosis. Issue 1 (2nd February 2020) - Harlow, Christopher Francis; Meghji, Jamilah; Martin, Laura; Harris, Timothy; Kon, Onn Min
Abstract : We present a case of a young Asian female with rheumatoid arthritis who received latent tuberculosis infection (LTBI) treatment prior to treatment with a biologic agent, and developed shock with resistant hypotension on re-exposure to rifampicin. We discuss the epidemiology, pathophysiology and management of rifampicin induced shock, concluding that clinicians should be aware of this rare, but potential adverse effect, and be aware that adverse reactions to rifampicin are more frequent during re-exposure or longer dosing interval regimes. The evidence for desensitisation following such a reaction is lacking and this approach is not currently recommended. We would suggest close collaboration between specialties prescribing immunosuppression and the tuberculosis team when LTBI treatment is required after a reaction, with patient involvement to discuss the risks and benefits of treatment options.